FUNDAMENTAL ANALYSIS, TECHNICAL ANALYSIS AND BROKER SUMMARY ANALYSIS IN INVESTING IN INDONESIAN STOCK MARKET BETWEEN 2016 - 2022 - Raditya, Alvin
The development of the Indonesian capital market is getting faster every year. This is demonstrated by the increasing rise of investors each year. However, choosing which stocks to buy and when to buy and sell these stocks is the major challenge encountered by investors. Analysis is thus required in order for investors in order to choose the right company by calculating the intrinsic value. Fundamental, technical, and broker summary analysis will be used in this study. These financial ratios are used in fundamental analysis to rank the filtered stocks including Return on Asset, Return on Equity, Price to Earnings, and Price to Book Value. Through technical analysis, the data is back tested between 2016 and 2022 using the Simple Moving Average, Weighted Moving Average dan Exponential Moving Average strategies. In the broker summary analysis, it will be seen which stocks are being accumulated or distributed by the broker. By choosing the right company and performing well (fundamental analysis) and determining the right time (technical analysis) to buy and sell the company's stocks, investors will get the maximum return. From the results of the study, the largest return was obtained by the Simple Moving Average method of 112.03%. Meanwhile, broker summary analysis is used as a tool to determine whether the stock price will go up or down. Investors must master these three analyses (fundamental, technical, broker summary) to be confident in their investments.